Education and Poverty: The Hypothesis of the Individualand Social Capital (2009)
The article reviews the theme of the poverty and the ways that it has been analyzed. After this, it makes a differentiation between the poverty and the exclusion and develops the main characteristics that the present programs of fight against the poverty